2018
DOI: 10.4269/ajtmh.18-0224
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Anthrax Outbreaks in Humans, Livestock, and Wildlife in the Same Locality, Kenya, 2014–2017

Abstract: Abstract.Epidemiologic data indicate a global distribution of anthrax outbreaks associated with certain ecosystems that promote survival and viability of Bacillus anthracis spores. Here, we characterized three anthrax outbreaks involving humans, livestock, and wildlife that occurred in the same locality in Kenya between 2014 and 2017. Clinical and epidemiologic data on the outbreaks were collected using active case finding and review of human, livestock, and wildlife health records. Information on temporal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
64
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 35 publications
6
64
0
1
Order By: Relevance
“…However, it is interesting to note that we did not find records of anthrax outbreaks in wildlife conservancies in agro-alpine regions of Kenya including the Aberdare and Mount Kenya national parks. This observation is consistent with our findings that more outbreaks occur during the dry season, and it may be explained by the similar associated risk factors [12]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, it is interesting to note that we did not find records of anthrax outbreaks in wildlife conservancies in agro-alpine regions of Kenya including the Aberdare and Mount Kenya national parks. This observation is consistent with our findings that more outbreaks occur during the dry season, and it may be explained by the similar associated risk factors [12]. …”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the world-famous annual wildebeest ( Connochaetes taurinus ) migration occurs between the Masai Mara and Serengeti national parks [11]. A recent study in Kenya reported three anthrax outbreaks over a period of 4 years in the same locality of Rift valley in Kenya that resulted in the death of 10.5% of all wildlife herbivores in a local national park, including 17% of the buffalos and 16% endangered black rhinos and white rhinos [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Handling carcasses of animals with suspected and con rmed anthrax has previously been established as a risk factor for cutaneous [19]. The location of the black eschars for most case-patients -on the hands and back -has also been observed in other studies demonstrating livestock-human transmission of anthrax [14], and is likely related to animal carcasses being carried over the shoulder.…”
Section: Discussionmentioning
confidence: 80%
“…One of the wards also bordered a game reserve. The sharing of grazing land with the game often results in the transmission of anthrax to livestock [26].…”
Section: Discussionmentioning
confidence: 99%